Congenital Ventricular Diverticulum or Aneurysm: A Difficult Diagnosis to Make - Lloyd Halpern; Carl Garabedian; Neil K. Worrall (Case Reports in Cardiology)
A pouch protruding from the free wall of the left ventricle may be either a congenital ventricular diverticulum (CVD) or aneurysm (CVA). Being aware of these rare congenital anomalies is critical in making the diagnosis. Differentiating the two is important for treatment decisions. We describe a patient with dextrocardia, Tetralogy of Fallot, and a congenital left ventricular apical diverticulum diagnosed following the induction of anesthesia. CVD and CVA may present in the antenatal period through late adulthood with differing morphology, location, and symptoms. Echocardiography is paramount in the diagnosis and characterization of these lesions. If this anomaly is encountered after the induction of anesthesia or during intraoperative echocardiography, the cardiothoracic anesthesiologist should make the surgical team aware so it can be further characterized and a treatment plan made prior to incision.